Cobit Framework Implementation 5 DSS Domain (Deliver, Service and Support) ITCC ITPLN Information Technology Governance Audit - Hendra Jatnika; Mochamad Farid Rifai; Riani Saputri Abadi; Muhammad Yaseer Maward; Martogi Johan Siagian (Eduvest - Journal of Universal Studies, 2025)
Information Technology Certification Center (ITCC) ITPLN is a certification unit that implements IT governance with Office 365 Applications. IT governance in Office 365 applications requires an audit to evaluate and assess capabilities and make recommendations on IT governance at ITCC. This is because the ITCC has never evaluated IT governance. Therefore, until now the ITCC does not know the extent of the benefits and impacts obtained from the application of IT on the progressivity of achieving goals related to information system management. ITCC also doesn't know what the weaknesses are and what the solutions are. The audit standard used is Control Objectives for Information and Related Technology (COBIT). The chosen COBIT 5 domain is the Deliver, Service, and Support (DSS) domain which focuses on the assessment of delivery and information technology services as well as its support for ongoing business processes including problem management so that the sustainability of business processes is maintained. In addition, it is also intended to control, evaluate, and plan long-term business processes. The result is the overall Capability Level on Office 365 in ITCC.